Kualitas Asap Cair Kayu Pelawan dan Tempurung Kelapa dengan Pemurnian Destilasi Sederhana - Mariyamah, Mariyamah; Wijayanti, Fitria; Oktasari, Ade (LPPM, Institut Teknologi Sepuluh Nopember, 2024)
Pelawan is a unique tree because all parts of its body, starting from the roots and stems to the tips of the branches, are red. Pelawan wood which is used by the community as firewood turns out to produce a liquid which is believed to be used for health. On the other hand, coconut shells are very abundant and are only used as charcoal. Pelawan wood and coconut shells are processed through pyrolysis at 450 °C to produce liquid smoke. The liquid smoke that has been obtained is subjected to a purification process. This study compares the quality of liquid smoke to SNI 8985:2021 and Japanese standards. The results show that the yield of liquid smoke from pelawan wood is 35% and coconut shell is 56.67%. Following the analysis of the chemical content of coconut shell liquid smoke, it has a bright yellow colour, no floating material, pH 3, specific gravity 1.0090 gr/cm3, 5.562% acid content and 0.014% phenolic content. Meanwhile, the chemical content of Pelawan Wood liquid smoke has colour, no floating matter, pH 2, specific gravity of 1.0096 gr/cm3, an acid content of 4.586% and a phenol content of 0.013%. The results of the analysis of the chemical content of the resulting liquid smoke meet SNI and Japanese standards.